Results 1 to 9 of 9

Math Help - Max/Min Application

  1. #1
    Senior Member
    Joined
    Jul 2008
    Posts
    347

    Exclamation Max/Min Application



    The parabola y = x^2 and the line y = mx +b intersect at the points A (α, α^2) and B (β, β^2) as shown.

    a) Explain why αβ = - b

    b) Show that AB = √ (m^2 + 4b) (m^2 + 1)

    c) The point P(x, x^2) lies on the parabola between A and B. Show that the area of triangle APB is given by:

    Area of Triangle APB = (b + mx x^2) √ (m^2 + 4b)

    d) Find the position of point P that maximizes the area of triangle APB in terms of m.


    Could someone please help me solve this problem?
    Follow Math Help Forum on Facebook and Google+

  2. #2
    Super Member
    earboth's Avatar
    Joined
    Jan 2006
    From
    Germany
    Posts
    5,830
    Thanks
    123
    Quote Originally Posted by xwrathbringerx View Post


    The parabola y = x^2 and the line y = mx +b intersect at the points A (α, α^2) and B (β, β^2) as shown.

    a) Explain why αβ = - b

    b) Show that AB = √ (m^2 + 4b) (m^2 + 1)

    c) The point P(x, x^2) lies on the parabola between A and B. Show that the area of triangle APB is given by:

    Area of Triangle APB = (b + mx x^2) √ (m^2 + 4b)

    d) Find the position of point P that maximizes the area of triangle APB in terms of m.


    Could someone please help me solve this problem?


    to #a):
    Use the 2-point-formula of a straight line:

    \dfrac{y-\alpha^2}{x-\alpha}=\dfrac{\beta^2-\alpha^2}{\beta-\alpha}

    y-\alpha^2=\dfrac{(\beta^2-\alpha^2)(x-\alpha)}{\beta-\alpha}

    y=\dfrac{((\beta-\alpha)(\beta+\alpha))(x-\alpha)}{\beta-\alpha}+\alpha^2

    y=(\beta+\alpha)x-\alpha \beta-\alpha^2+\alpha^2

    y=(\beta+\alpha)x-\alpha \beta Compare this equation with

    y=m \cdot x+b which gives b = - \alpha \beta
    Follow Math Help Forum on Facebook and Google+

  3. #3
    Super Member
    earboth's Avatar
    Joined
    Jan 2006
    From
    Germany
    Posts
    5,830
    Thanks
    123
    Quote Originally Posted by xwrathbringerx View Post


    The parabola y = x^2 and the line y = mx +b intersect at the points A (α, α^2) and B (β, β^2) as shown.
    ...
    d) Find the position of point P that maximizes the area of triangle APB in terms of m.


    Could someone please help me solve this problem?
    The area of the triangle is a function with respect to x. Calculate the first derivation and set this term equal to zerO.

    A(x)=\dfrac12(b+mx-x^2)\underbrace{\sqrt{m^2+4b}}_{constant!}

    A'(x)=\dfrac12 \sqrt{m^2+4b} \ \cdot \ (m-2x)

    A'(x) = 0~\implies~m-2x=0~\implies~x=\dfrac m2
    Follow Math Help Forum on Facebook and Google+

  4. #4
    Senior Member
    Joined
    Jul 2008
    Posts
    347
    Sorry but how do I find the area of the triangle APB?
    Follow Math Help Forum on Facebook and Google+

  5. #5
    Banned
    Joined
    Aug 2008
    Posts
    530
    Quote Originally Posted by xwrathbringerx View Post


    The parabola y = x^2 and the line y = mx +b intersect at the points A (α, α^2) and B (β, β^2) as shown.

    a) Explain why αβ = - b

    b) Show that AB = √ (m^2 + 4b) (m^2 + 1)
    b) From part a) you got, \alpha\beta=-b

    Also, slope of given line (y=mx+b) = slope of AB

    m = \frac{\beta^2-\alpha^2}{\beta-\alpha}=\beta+\alpha

    Now, use distance formula to calculate distance AB= \sqrt{(x_2-x_1)^2+(y_2-y_1)^2}

    AB=\sqrt{(\beta-\alpha)^2+(\beta^2-\alpha^2)^2}

    AB=\sqrt{(\beta-\alpha)^2+(\beta-\alpha)^2(\beta+\alpha)^2}

    AB=\sqrt{(\beta-\alpha)^2+(\beta-\alpha)^2m^2}

    AB=\sqrt{(\beta-\alpha)^2(1+m^2)}

    Now,

    (\beta-\alpha)^2 = \beta^2-2\alpha\beta+\beta^2

    = \beta^2+2\alpha\beta+\beta^2-4\alpha\beta

    =(\beta+\alpha)^2-4\alpha\beta

     =m^2-4(-b)=m^2+4b

    (\beta-\alpha)^2=m^2+4b


    Therefore,

    AB=\sqrt{(\beta-\alpha)^2(1+m^2)} = \sqrt{(m^2+4b)(1+m^2)}
    Follow Math Help Forum on Facebook and Google+

  6. #6
    Banned
    Joined
    Aug 2008
    Posts
    530
    Quote Originally Posted by xwrathbringerx View Post


    The parabola y = x^2 and the line y = mx +b intersect at the points A (α, α^2) and B (β, β^2) as shown.

    c) The point P(x, x^2) lies on the parabola between A and B. Show that the area of triangle APB is given by:

    Area of Triangle APB = (b + mx – x^2) √ (m^2 + 4b)
    AB is the base of triangle, and perpendicular distance from P to AB is height of triangle.

    Height = Perpendicular distance from P(x, x^2) to line mx + b - y = 0

    = \frac{|mx + b - x^2|}{\sqrt{1^2+m^2}}

    = \frac{|mx + b - x^2|}{\sqrt{1+m^2}}

    Area of triangle = \frac{1}{2}\times base \times height

    =  \frac{1}{2}\times AB \times height

    =\frac{1}{2}\times \sqrt{(m^2+4b)(1+m^2)} \times \frac{|mx + b - x^2|}{\sqrt{1+m^2}}

    =\frac{1}{2}(mx + b - x^2) \sqrt{(m^2+4b)}

    Area,\;\;A(x)=\frac{1}{2}(mx + b - x^2) \sqrt{(m^2+4b)}
    Follow Math Help Forum on Facebook and Google+

  7. #7
    Banned
    Joined
    Aug 2008
    Posts
    530
    Quote Originally Posted by xwrathbringerx View Post

    d) Find the position of point P that maximizes the area of triangle APB in terms of m.

    d) The area of the triangle is a function with respect to x. Calculate the first derivation and set this term equal to zero

    Area,\;\;A(x)=\frac{1}{2}(mx + b - x^2) \sqrt{(m^2+4b)}

    A(x)=\dfrac12(mx+b-x^2)\underbrace{\sqrt{m^2+4b}}_{constant!}

    A'(x)=\dfrac12 \sqrt{m^2+4b} \ \cdot \ (m-2x)

    A'(x) = 0~\implies~m-2x=0~\implies~x=\dfrac m2

    <br />
Point \;\;P(x, x^2)=\left(\frac{m}{2}, \frac{m^2}{4}\right)

    Did you get all the parts NOW ???
    Follow Math Help Forum on Facebook and Google+

  8. #8
    Senior Member
    Joined
    Jul 2008
    Posts
    347
    *scratches head*

    How exactly does become ?

    Is m - 2x the factorised form of mx + b - x^2?
    Follow Math Help Forum on Facebook and Google+

  9. #9
    Super Member
    earboth's Avatar
    Joined
    Jan 2006
    From
    Germany
    Posts
    5,830
    Thanks
    123
    Quote Originally Posted by xwrathbringerx View Post
    *scratches head*

    How exactly does become ?

    Is m - 2x the factorised form of mx + b - x^2?
    I have calculated the first derivation of A. Since a constant factor stays unchanged I have marked the constant factor, meaning: Don't touch me!

    Therefore you only have to derive (mx+b-x^2) with respect to x (the derivation of b wrt x is zero):

    \dfrac{d(mx+b-x^2)}{dx }= m-2x
    Follow Math Help Forum on Facebook and Google+

Similar Math Help Forum Discussions

  1. Replies: 1
    Last Post: October 9th 2008, 04:17 AM
  2. application 3
    Posted in the Calculus Forum
    Replies: 1
    Last Post: March 18th 2007, 03:36 AM
  3. application 2
    Posted in the Calculus Forum
    Replies: 1
    Last Post: March 18th 2007, 03:30 AM
  4. application 2
    Posted in the Calculus Forum
    Replies: 1
    Last Post: March 14th 2007, 06:38 AM
  5. application
    Posted in the Calculus Forum
    Replies: 1
    Last Post: March 14th 2007, 04:58 AM

Search Tags


/mathhelpforum @mathhelpforum